2022
DOI: 10.1007/s10964-022-01685-3
|View full text |Cite
|
Sign up to set email alerts
|

A Daily Examination of the Moderating Role of Adolescents’ Coping in Associations between Psychologically Controlling Parenting and Adolescents’ Maladjustment

Abstract: To explain why there is substantial heterogeneity in the degree to which adolescents suffer from psychologically controlling parenting, it is important to take into account adolescents' active contribution to the socialization processes and to their coping with controlling parenting in particular. This study aimed to examine whether adolescents' coping with controlling parenting (i.e., oppositional defiance, compulsive compliance, negotiation, and accommodation) moderated associations between psychologically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Moreover, girls typically demonstrate greater compliance and often prioritize preserving harmonious relationships over directly expressing their own feelings [53]. One study found that adolescents' coping styles (i.e., accommodation and compulsive compliance) played a moderating role in buffering the daily negative consequences associated with psychologically controlling parenting [54]. Therefore, in the present study, it is possible that girls' obedience played an adaptive role in buffering the negative effects of psychological control and decreasing their externalizing problems.…”
Section: The Relationship Between Parental Psychological Control and ...mentioning
confidence: 65%
“…Moreover, girls typically demonstrate greater compliance and often prioritize preserving harmonious relationships over directly expressing their own feelings [53]. One study found that adolescents' coping styles (i.e., accommodation and compulsive compliance) played a moderating role in buffering the daily negative consequences associated with psychologically controlling parenting [54]. Therefore, in the present study, it is possible that girls' obedience played an adaptive role in buffering the negative effects of psychological control and decreasing their externalizing problems.…”
Section: The Relationship Between Parental Psychological Control and ...mentioning
confidence: 65%